Interferon Gamma Release Assay sebagai Diagnosis Infeksi Laten Mycobacterium tuberculosis - Evriana Citra (CV. Jasa Sukses Abadi, 2020)
Mycobacterium tuberculosa (Mtb) infection is influenced by host-specific factors and pathogens interacting with the environment in a complex way to determine the outcome of infection. The result of infection with Mycobacterium tuberculosa is one of three possible outcomes, which are cured, latent, or active. asymptomatic latent tuberculosis infection, which is defined as a state of persistent bacterial viability, immune control, and no evi- dence of clinically manifested active tuberculosis. Latent tuberculosis infection (LTBI) is a persistent immunological evidence in the asymptomatic phase of active TB infection. LTBI can develop into active TB that depends on host factors, pathogens and the environment. The diagnosis of LTBI can reduce the rate of active TB by providing preventive therapy. At present one of the checks that can diagnose LTBI is the examination of Interferon Gamma Release Assay (IGRA) in addition to the tuberculin skin test (TST). The purpose of this study was to determine the specificity and sensitivity of the IGRA examination as a diagnosis of latent Mycobacterium tuberculosis infection. The result is IGRA examination is more specific and sensitive, unless active with TST that is unable to determine active TB or not